Chondrosarcoma mimicking an adnexal mass: A very rare case report - Özcan, Hüseyin Çağlayan (Turk J Obstet Gynecol, 2017)
Chondrosarcoma is considered as a common primary bone sarcoma. These sarcomas can form large masses without any specific symptoms because there are no barriers in pelvic anatomy to prevent the enlargement of tumors, and can mimic ovarian masses. We present a pelvic chondrosarcoma in a woman aged 37 years who was misdiagnosed as having an ovarian mass due to the limited information obtained from imaging studies. Pelvic chondrosarcoma should be considered in patients who have pelvic masses with solid components. It should be kept in mind that interventions should be performed at centers where there are orthopedic surgeons with experience of this subject.